The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/cbdv.201900588
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated and Very‐Long‐Chain Fatty Acids Are Involved in the Adaptation of Maloideae (Rosaceae) to Combined Stress in the Mountains

Abstract: One of the mechanisms of plant adaptation to combined stress under conditions of altitudinal zonation is changing the lipid fatty acid (FA) composition. The main changes in the FA composition occurred in the outer cell layers of the pericarp, but not in the parenchyma. Adaptation was found to be species-specific. In Cydonia oblonga MILL. and Malus domestica BORKH., the ratio of polyunsaturated 18:2 and 18:3 lipid FAs changed with increasing height, while a constitutive level of the unsaturation index (UI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Besides, the study of these fruits from Serbia confirmed that the main volatile compounds in green and ripe fruits were hexanal and (E)-2-hexenal i.e., hexanol and (Z)-3-hexenol, respectively [7]. Among fatty acids, saturated ones, such as hexanoic and hexadecanoic acids, were predominant [7,8], as well as stearic, oleic, linoleic, and behenic acids [8]. The specificity of medlar fruit is that it can be eaten after some period of ripening when it becomes soft and dark.…”
Section: Introductionmentioning
confidence: 84%
“…Besides, the study of these fruits from Serbia confirmed that the main volatile compounds in green and ripe fruits were hexanal and (E)-2-hexenal i.e., hexanol and (Z)-3-hexenol, respectively [7]. Among fatty acids, saturated ones, such as hexanoic and hexadecanoic acids, were predominant [7,8], as well as stearic, oleic, linoleic, and behenic acids [8]. The specificity of medlar fruit is that it can be eaten after some period of ripening when it becomes soft and dark.…”
Section: Introductionmentioning
confidence: 84%
“…The zones with FAMEs were visualized in UV light (λ = 365 nm). Then, the silica gel from the FAME zone of the chromatographic plate was transferred to a Schott glass filter, and the FAMEs were eluted from the sorbent by washing with C6Н14 six times [49].…”
Section: Preparation Of Fatty Acid Methyl Estersmentioning
confidence: 99%